Digital Communities in a Networked Society e-Commerce, e-Business and e-Government - Mendes, Manuel J.; Suomi, Reima.; Passos, Carlos. (IFIP International Federation for Information Processing, 2004)
Digital Communities in a Networked Society: e-Commerce, e-Business and e-Government deals with the accelerating evolution in the computerization of society. This evolution, or should we call it a revolution, is dominantly driven by the Internet, and documented by the novelties introduced, year by year, by Information and Communication Technologies. The book contains recent results of research and development in the areas of: -E-government, -Business models of e-applications, -Innovative structures in the internet, -Auctions and e-payment, -Future aspects of communication, -Internet and the web, -Advanced platforms and grid computing, -Cooperation and integration, -Modeling and construction of e-services.